Spatial and temporal changes and influencing factors of urban ecological efficiency in the Yellow River Basin - Qian-Ming, Zhang; Ji-Xia, Li (Frontiers in Environmental Science, 2024)
The Yellow River Basin serves as a vital ecological shield for China, and enhancing the urban ecological efficiency (UEE) is essential for the region's ecological civilization and high-quality development. This research employs the slacks-based measure-data envelopment analysis (SBM-DEA), which incorporates undesirable outputs, and the Malmquist index to measure the UEE of 65 cities in the Yellow River basin from 2008 to 2017, described its spatio-temporal evolution characteristics, and utilizes its influencing factors using the Bootstrap truncated regression model. The main findings are as follows. ① The UEE in the Yellow River Basin has seen a steady, albeit low, increase from 2008 to 2017, with notable disparities existed in the upper, middle and lower reaches. Low pure technical efficiency is the main factor limiting the improvement of UEE in the Yellow River Basin. ② Cities with higher ecological efficiency in the Yellow River Basin generally exhibit a spatial distribution pattern of "lower reaches > middle reaches> upper reaches", and it shows that cities with growing UEE are continuously shifting to the middle and lower reaches. ③ Environmental regulation, scientific and educational investment, economic scale, and greening level significantly promote the improvement of UEE in the Yellow River Basin, but population density and industrial structure lead to a decline in UEE. However, this result is heterogeneous between the upper, middle, and lower reaches, such as environmental regulation hindering the growth of UEE in the upper reaches, scientific and educational investment hindering the improvement of UEE in the downstream areas, and industrial structure significantly enhancing UEE in the midstream areas. These findings offer valuable insights for policymakers aiming to address ecological challenges and promote sustainable development within the Yellow River Basin, highlighting the need for targeted strategies that consider regional differences and the unique characteristics of each reach.